JURNAL REHSOS VOL 5 NO 2 2023: COPING STRATEGY LANJUT USIA DALAM PEMENUHAN KEBUTUHAN PADA MASA PANDEMI COVID-19 DI KELURAHAN SINDANGKASIH KECAMATAN PURWAKARTA KABUPATEN PURWAKARTA - Catur Herry (Jurnal Ilmiah Rehabilitasi Sosial (Rehsos), 2023)
This research is motivated by the problems of the elderly, who have difficulty fulfilling their daily needs properly. This study aims to obtain an overview of the coping strategies carried out by the elderly in meeting their basic needs, namely clothing, housing, and food, during the COVID-19 pandemic in Sindangkasih Village, Purwakarta District, Purwakarta Regenc. A coping strategy has two aspects, namely emotional-focused coping and problem- focused coping. The research method used is qualitative, with data collection techniques being interviews, observation, and documentation studies. The informants in this study were three elderly people in Sindangkasih Village, Purwakarta District, Purwakarta Regency. The results showed that the coping strategies carried out by the elderly in the sub-aspects of accepting responsibility and planned problem solving have not been carried out properly. Acceptance that is too high for the problems faced by the elderly has an impact on the absence of efforts made by the elderly to solve the problem in a planned manner.